High-Performance Hybrid Asymmetric Supercapacitors with rGO/α-Fe2O3 and rGO/TiO2 Nanocomposites - Zeinab Abbasali KarajAbad; Adrine Malek Khachatourian; Mohammad Golmohammad; Ali Nemati (Iranian Journal of Materials Science and Engineering)
Hybrid asymmetric supercapacitors using distinct cathode/anode materials offer enhanced energy density by expanding operational potential windows compared to symmetric configurations. In this work rGO/α-Fe₂O₃ and rGO/TiO₂ nanocomposites were synthesized via hydrothermal method for hybrid asymmetric supercapacitors applications. Field emission scanning electron microscope (FESEM) revealed uniform distribution of spherical α-Fe₂O₃ and TiO₂ nanoparticles on rGO sheets. The X-ray diffractometry (XRD) analysis confirmed the presence of the hematite and anatase in the rGO/α-Fe2O3 and rGO/TiO2 nanocomposites, respectively. Additionally, in the XRD spectra of both nanocomposites, a broad peak corresponding to the (002) crystalline planes of rGO was observed. Electrochemical testing showed specific capacities of 130 F/g (rGO/α-Fe₂O₃) and 253 F/g (rGO/TiO₂) at 5 mV/s in 1M KOH. The assembled hybrid asymmetric supercapacitors (rGO/α-Fe₂O₃//rGO/TiO₂) achieved a 1.6 V operational potential window. Power density and energy density of 1066 W kg-1 and 9.7 Wh kg-1 were achieved at a current density of 1 A/g, respectively.